Grooming and social cohesion in primates: a comment on Grueter et al. - Dunbar, R; Lehmann, J (2013)
Grueter et al. have recently claimed that grooming time in primates is best explained by terrestriality, which they take to be a proxy for hygiene demand. We suggest that their results arise from a confound between terrestriality and other aspects of sociality, combined with a number of conceptual and sampling problems. © 2013 Elsevier Inc. All rights reserved.